Conhecimento e percepção da população sobre bem-estar animal, guarda responsável e maus-tratos a cães. - Gabriela Ferreira Siano (2022)
Companion animals, especially dogs, are present in most Brazilian households and this relationship between humans and dogs establises a situation of dependence for theses animals on the resources provided by the responsible guardian. The care provided by the animal's owner will affect its welfare, since it is determined by the animal’s physical and psychological conditions, as a result of its ability to cope with the environment. When this relationship occurs in a dysfunctional way and the dog's owner fails to provide for its basic needs, the dog may present a low or very low welfare state that implies a case of mistreatment of the animal. Therefore, the population's knowledge about the components of animal welfare and responsible ownership, which are connected to animal abuse, is important in this context. That said, this study aimed to evaluate the lay population's level of knowledge about animal welfare, responsible ownership and abuse of dogs alongside the indicators of the animal welfare investigation protocol used to characterize situations of abuse, and to compare the population's perception with sociodemographic indicators. A portion of the indicators (16%), all in the comfort indicators category, presented between 20 and 37% of regular responses. Only 5% of the indicators, present in the behavior category, presented a small but important percentage (13.7%) of inadequate responses. The sociodemographic factor that had a significant influence on many adequate responses was the female gender. While the male gender showed a significant influence for the regular response in comfort indicators. Factors such as income and education exerted an influence on few items within different categories, not representing an important factor for the population's level of knowledge. In general, the level of population’s knowledge achieved was considered adequate, with most indicators presenting adequate responses, with 79% of the indicators evaluated showing adequate response rates above 90%.